Safeguarding China’s threatened cycads: Strategies to combat alarming habitat degradation and anthropogenic collection pressure - Chunping Xie; C. Y. Jim (Nature Conservation)
Cycads (Cycas L.) are ancient plants of immense ecological and evolutionary significance, yet they now face escalating threats to their survival. Around 20 cycad species remain in China, beset with highly restricted distributions and small, fragmented, declining and threatened populations. Despite strengthened legal protection and recent conservation efforts, these plants continue to suffer from habitat destruction and anthropogenic collection pressure. Infrastructure projects, including road construction and agricultural expansion, have fragmented and degraded critical cycad habitats. Concurrently, the rise of e-commerce platforms has facilitated unregulated online collection and trade, complicating enforcement. This manuscript addresses these challenges and proposes a comprehensive conservation strategy. They include enhancing habitat protection through establishing buffer zones, creating a community-based “Cycad Safeguarding Network” and using advanced information technologies, such as artificial intelligence and blockchain for precision monitoring and enforcement. Integrating modern scientific tools with an integrated conservation strategy can safeguard China’s cycads and provide a model for protecting other threatened plant species globally.